RANCANG BANGUN ALAT MONITORING KEMIRINGAN PADA LANTAI BERBASIS GOOGLE SHEETS - Anggraeni, Aprilia Putri; Wisaksono, Arief; Falah, Agus Hayatal; Saputra, Dwi Hadidjaja Rasjid (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
Currently, the property sector—particularly residential housing—presents considerable business opportunities. A critical structural component of any residential building is the floor, which serves as the foundational surface for human activity such as walking, standing, and other daily operations. In some cases, floor surfaces may exhibit undetectable inclinations that could compromise structural integrity over time. To address this issue, the development of a technological system for detecting floor tilt is essential. This study proposes a real-time floor tilt monitoring system utilizing tilt and accelerometer sensors, integrated with Google Sheets for cloud-based data visualization and logging. Sensor data is transmitted automatically via an Internet of Things (IoT) platform, enabling continuous monitoring without manual intervention. The recorded data is organized and displayed in tabular form within Google Sheets to facilitate visual analysis and interpretation.The proposed system offers an efficient, scalable, and cost-effective solution for early detection of floor inclination and potential structural degradation. By providing real-time insights, it supports proactive building maintenance and enhances occupant safety by enabling timely responses to structural anomalies.